Sobressalto patológico: aspectos clínicos e eletrencefalográficos Startle seizures: clinical and electroencephalographic studies - Frederico Dahne Kliemann; Nelson Pires Ferreira (Arquivos de Neuro-Psiquiatria)
Os autores relatam o caso de um paciente apresentando crises de sobressalto provocadas por estímulos auditivos, sensitivos e visuais, sem crises epilépticas espontâneas nem retardo psicomotor. Estudam os aspectos clínicos e eletrencefalográficos e revisam a situação da entidade entre as assim chamadas epilepsias reflexas. The case of a patient presenting startle seizures provoked by acoustic, sensitive and visual stimuli who did not present spontaneous epileptic seizures and had no psychomotor retard is reported. The clinical and electroencephalographic aspects with special mention to the finding of exaggerated evoked potentials in the vertex are discussed. The situation of the disease among reflex epilepsies is revised.